B cell encounters with apoptotic cells. (August 2013) - Bekeredjian-Ding, Isabelle
<x xml:space="preserve">Abstract</x> Autoantibodies directed against nuclear antigens often arise in autoimmune disease associated with the failure to clear apoptotic cells in a swift and timely manner. Nucleic acids present in apoptotic cells and in membranous microparticles derived thereof exert adjuvant activity in the immune response to apoptosis. The scope of this review is to provide an overview on the current knowledge on B cell responses to apoptotic cells and membranous microparticles. Although physiological B cell responses to apoptotic cells result in the release of IL-10 by B cells and immunosuppression, pathological responses lead to autoantibody formation. Toll-like receptors specific for nucleic acids are engaged in both types of responses. In this review we delineate the functional impact of nucleic acids on B cell responses in the context of apoptosis.